Detection of anatoxin-producing Phormidium in a New Zealand farm pond and an associated dog death. Issue 1 (2nd January 2017) - Wood, Susanna A.; Puddick, Jonathan; Fleming, Rebecca; Heussner, Alexandra H.
ABSTRACT: Over the last decade, proliferations of benthic mat-forming Phormidium have been reported with increasing frequency in New Zealand's cobble-bed rivers. The dominant species within these mats ( Phormidium autumnale ) commonly produces a range of neurotoxins, collectively known as anatoxins. Ingestion of toxic Phormidium -dominated mats has resulted in the death of an estimated 100 dogs at New Zealand's rivers since 2005. In September 2014, a 12-week-old border terrier died rapidly after contact with floating 'algal mats' at a small farm pond near Kaikoura (South Island, New Zealand). The aim of this study was to establish whether ingestion of the algal mats was the cause of the death and if the dominant species was similar to that found in rivers. Environmental samples from the pond and the dog's stomach contents contained moderate levels of anatoxin- a (25 µg L −1 and 36 µg kg −1 wet weight, respectively) and high levels of dihydroanatoxin- a (2, 118 µg L −1 and 4, 437 µg kg −1, respectively). The dominant organism in the environmental sample was cultured and a polyphasic approach used for characterisation. Morphological analysis of environmental samples and six isolates indicated the dominant species was most similar to Ph. autumnale. Further confirmation was provided by 16S ribosomal RNA gene sequences which showed a high percentage identity (≥ 99%) to strains isolated from Phormidium -dominated mats in New Zealand rivers. Identification of anatoxin- a and dihydroanatoxin- a in the stomach contents, environmental samples and isolates, in concert with the rapid dog death provide strong evidence that anatoxin poisoning was the cause of death. To our knowledge this is the first report in New Zealand of a dog death related to ingestion of toxic Phormidium mats from a farm pond. This study highlights the wide diversity of habitats that toxin-producing Phormidium can inhabit, and the need for greater awareness of the risks Phormidium -dominated mats pose to human and animal health.